Exit west : - Hamid, Mohsin (Penguin, 2017)
"From the internationally bestselling author of The Reluctant Fundamentalist and How to Get Filthy Rich in Rising Asia, a love story that unfolds in a world being irrevocably transformed by migration. In a country teetering on the brink of civil war, two young people meet--sensual, fiercely independent Nadia and gentle, restrained Saeed. They embark on a furtive love affair, thrust into premature intimacy by the unrest roiling their city. When it explodes, turning familiar streets into a patchwork of checkpoints and bomb blasts, they begin to hear whispers about doors--doors that can whisk people far away, if perilously and for a price. As violence and the threat of violence escalate, Nadia and Saeed decide that they no longer have a choice. Leaving their homeland and their old lives behind, they find a door and step through. Exit West is an epic compressed into a slender page-turner--both completely of our time and for all time, Mohsin Hamid's most ambitious and electrifying novel yet"--